Modelling the impact of mosquito bed net utilization on malaria transmission and evolution of pyrethroid resistance - Ivan Sseguya; Joseph Y. T. Mugisha; Juliet N. Nakakawa; Prashanth Selvaraj; Jonathan Kayondo (PLoS ONE, 2026)
Long-lasting Insecticide Nets (LLINs) are central to malaria prevention, but their effectiveness is threatened by the increasing pyrethroid resistance and low bed net utilization in malaria-endemic regions globally. This study formulates a genotype-specific compartmental model accounting for malaria transmission. It incorporates the blocking and insecticidal killing effects of LLINs, and pyrethroid-induced fitness costs, to evaluate the impact of LLIN utilization on malaria and resistance dynamics. Reproductive numbers with and without LLINs were derived, and sensitivity analysis performed. This analysis showed that the utilization of LLINs and their effectiveness against pyrethroid-resistant vectors have the strongest effect in reducing malaria transmission in both Sobol and partial rank correlation coefficient PRCC analyses. The baseline scenario and four LLIN utilization scenarios (standard, three-year, two-year and one-year) were simulated over nine years to track malaria transmission, mosquito population and evolution of resistance. These were assessed, with pyrethroid-only nets deployed in the first two campaigns and pyrethroid piperonyl butoxide (PBO) nets deployed in the third campaign. Results showed that, despite an initial LLIN coverage of 81%, protection against malaria infection by both pyrethroid-only and pyrethroid-PBO nets was not sustained over the campaign period and this worsened with lower utilization levels. Pyrethroid-PBO nets provided greater mosquito suppression and better protection under standard utilization, but their advantage over pyrethroid-only nets declined with lower utilization. The study further demonstrated that repeated pyrethroid-only campaigns accelerate the evolution of pyrethroid resistance, but PBO nets counteract this trend particularly when such resistance carries a higher fitness cost. Although lower utilization levels slowed resistance evolution, these scenarios do not represent an epidemiologically viable malaria control strategy.